Analysis of aluminium brazing sheet differential scanning calorimetry data. (2017) - Benoit, Michael J.; Whitney, Mark A.; Wells, Mary A.; Penlidis, Alexander; Corbin, Stephen F.; Winkler, Sooky
Differential scanning calorimetry (DSC) measurements have provided insight into metallurgical reactions which can occur during joining of Al brazing sheet. Researchers have claimed that DSC is sensitive enough to differentiate between brazing sheets with different initial conditions; however, no rigorous proof of this claim has been given. The sensitivity of DSC measurements, as measured by changes in melting peak area, to experimental factors such as DSC sample preparation, sample orientation during testing and starting sheet temper has been investigated. A 2 3 factorial design was used, and the results were analysed using analysis of variance. The results showed that only the sheet punching direction during sample preparation had a statistically significant influence on the DSC measurements. Microstructure analysis revealed that punching on the core layer of the sheet led to extra clad alloy on the side of the sample, which melted during heating and contributed to a greater measured melting peak area.